2016
DOI: 10.1021/acscentsci.6b00293
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling Photochemical Relationships Among Natural Products from Aplysia dactylomela

Abstract: Aplydactone (1) is a brominated ladderane sesquiterpenoid that was isolated from the sea hare Aplysia dactylomela together with the chamigranes dactylone (2) and 10-epi-dactylone (3). Given the habitat of A. dactylomela, it seems likely that 1 is formed from 2 through a photochemical [2 + 2] cycloaddition. Here, we disclose a concise synthesis of 1, 2, and 3 that was guided by excited state theory and relied on several highly stereoselective transformations. Our experiments and calculations confirm the photoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…It recorded a 50% inhibition at 45.4 and 92.4 µmol/L for both the cell lines respectively [58]. Aplydactone (60) was isolated from specimens of Nosy Hara, off the coast of Madagascar [59]. It possesses a highly strained, tetracyclic skeleton with three quaternary stereocenters, which are all embedded in the ladderane substructure [60].…”
Section: Charmigrane Type Skeletonmentioning
confidence: 99%
See 3 more Smart Citations
“…It recorded a 50% inhibition at 45.4 and 92.4 µmol/L for both the cell lines respectively [58]. Aplydactone (60) was isolated from specimens of Nosy Hara, off the coast of Madagascar [59]. It possesses a highly strained, tetracyclic skeleton with three quaternary stereocenters, which are all embedded in the ladderane substructure [60].…”
Section: Charmigrane Type Skeletonmentioning
confidence: 99%
“…Aplydactone (60) was isolated from specimens of Nosy Hara, off the coast of Madagascar [59]. It possesses a highly strained, tetracyclic skeleton with three quaternary stereocenters, which are all embedded in the ladderane substructure [60]. It is assumed that dactylone (85) is converted to aplydactone (60) via photochemical addition due to the intense solar irradiation the sea hare is exposed to.…”
Section: Charmigrane Type Skeletonmentioning
confidence: 99%
See 2 more Smart Citations
“…Later Tr auner et al also independently reported their interesting findings in photochemical relationships among brominated sesquiterpenes from Aplysia dactylomela. [7] Herein we report aconcise synthesis of 1 and it is greatly facilitated by an unusual late-stage,r emote C À H functionalization. [8] Theu nprecedented structure of aplydactone inspired us to pursue as trategically unique pathway.A so utlined in Figure 1b,weenvisioned that the brominated carbon stereocenter (C8) of 1 could arise from as tereoselective hydrogenation of the vinyl bromide function (C8 À C9) of the advanced precursor 3.T he bridged cyclohexanone ring in 3 (highlighted with bold lines) could be forged by an intramolecular carbenoid CÀHinsertion [9] from the a-diazoketone 4 which bears a[2]-ladderane scaffold (6/4/4 tricyclic system).…”
mentioning
confidence: 99%